INVENTARISASI JENIS-JENIS TUMBUHAN OBAT PADA PENGOBATAN TRADISIONAL DI KECAMATAN ENOK KABUPATEN INDRAGIRI HILIR SEBAGAI RANCANGAN MODUL BIOLOGI SMA - Dias Setyawan; Nursal '; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstark : A research was conducted in November to August 2016 to collect data on types of medicinal plants from traditional cure in Enok Sub-district Indragiri Hilir Regency. This research consists of 2 stages. The first stage is collecting data of medicinal plants by survey method (interview and field observation). Data which were obtained are analyzed by descriptive method. The second stage is designing learning module of biology as a result of the research. The study found 110 species from 53 families of medicinal plants used in traditional medicine in Enok, Indragiri Hilir District. Family of medicinal plants that is widely taken is Zingiberaceae (11 species); also, habitus of medicinal plants widely used are herbs, 42 species. There are 51 species of medicinal plants found in the yard, and 63 species, which are believed, are able to cure many diseases particularly digestive system. The research also shows that 47.5% of medicinal plant parts utilized are leaves, while the treatment of medicinal plants widely used is boiled (48.5%), and drinking is the popular way to take this medicine (56.8%). 5 out of 110 types of potential plants are found in this area. Unfortunately, these plants are still strange from the society. Based on the potential analysis of high school biology syllabus, there are 8 basic competencies related to the research result and can be developed as a source of learning design of one of the modules on the concept of biodiversity utilization.Keywords : Inventory, Medicinal Plant, Enok District, Module Design